Synthesis and characterization of NCL-5, NCL-6 and NCL-7: new zeolites enriched with polymorph B of the BEA family - Kadgaonkar, Mahesh D.; Kasture, Mahesh W.; Bhange, Deu S.; Joshi, Praphulla N.; Ramaswamy, Veda; Gupta, Narendra M.; Kumar, Rajiv (Microporous and Mesoporous Materials, 2007)
The synthesis of all-silica analogs of polymorph B-enriched zeolites of the BEA family denoted as NCL-5, NCL-6 and NCL-7 was realized hydrothermally at lower water content in fluoride medium using perchloric acid as promoter and terraethylammonium hydroxide as template. The present article explains the effect of different synthesis parameters on NCL-5, NCL-6 and NCL-7. The samples were characterized using XRD, low temperature N-2-adsorption, Si-29 MAS NMR and FTIR spectroscopy. The phase composition of the structures was derived using simulated patterns for the random intergrowths of polymorphs A and B using DIFFaX Code. The stacking direction c' is perpendicular to the a'b' plane of the layer. The phase composition of polymorph B derived using DIFFaX code was found to be 90-95%. 70-75% and 60-65% in NCL-5, NCL-6 and NCL-7, respectively. The gradual decrease of polymorph B concentration in these samples showed a correlation with the decrease in water/SiO2 molar ratio in gel. The framework FTIR spectral analysis of NCL-5 and all-silica-beta supported the postulation that significant enrichment of polymorph B in NCL-5 compared to that in all-silica-beta, as indicated by the relative intensities of pair of bands at 1097 and 1018 cm(-1) and 460 and 423 cm(-1) vibrations, leads to more tortuous channel structure associated with polymorph B. (C) 2007 Elsevier Inc. All riahts reserved.
Keywords: BEA family; NCL-5; NCL-6; NCL-7; polymorph B enrichment; synthesis; zeolites

Structural features of Penicillin acylase adsorption on APTES functionalized SBA-15 - Shah, Pallavi; Sridevi, N.; Prabhune, Asmita; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2008)
The immobilization of Penicillin acylase (PGA) enzyme (which belongs to the Ntn hydrolase super family) into the amino-functionalized SBA-15 mesoporous molecular sieve is carried out to see the effect of silica as a host matrix on the enzyme kinetics. Physicochemical characterization by nitrogen adsorption, powder XRD and TEM methods indicate that the characteristic hexagonal features and the original pore structure of the parent SBA-15 is retained even after the incorporation of PGA. The adsorption of PGA on SBA15 shows a dependence on the pore volume and the composition of the adsorbent. The maximum loading of the enzyme was observed at pH 7.8, slightly below the isoelectric point of the enzyme. The loading capacity of immobilized PGA is 34 mg protein per 0.5 g of SBA-15. The trapped enzyme is more stable than the soluble form to temperature and pH environments and retained 73% of its activity after immobilization. This enhanced stability is attributed to the protective nature of the cage itself and to the rigidity of the SiO(2) matrix, which reduces the freedom of peptide-chain refolding of molecular motions that occur in denaturation processes. The strength of binding is very strong; however, the activity of the immobilized enzyme is then simply restored with very little leakage of enzyme from the support. An important feature of the immobilized PGA enzyme is the excellent reusability without significant loss in activity, which indicates potentially exciting industrial/biomedical application of this support. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Penicillin G acylase; PGA immobilized SBA-15; pH and temperatures stability; SBA-15

Synthesis, characterization and catalytic activity of Sn-SBA-15 mesoporous molecular sieves - Ramaswamy, Veda; Shah, Pallavi; Lazar, Karoly; Ramaswamy, A. V. (Catalysis Surveys from Asia, 2008)
Our recent reports on the synthesis of Sn-incorporated mesoporous SBA-15 materials have been reviewed. The preparation of the samples with different Si/Sn ratios followed two procedures, the first is the post-synthesis modification of SBA-15 by impregnation with Sn chloride or acetate, and the second is the direct method in which Sn chloride was introduced in to Si precursor along with amphiphilic triblock copolymer, while varying the ratio of the synthesis gel. Detailed characterization of the Sn-SBA-15 samples by a variety of techniques shows how the synthesis procedures influence the properties of the samples that reflect on the differences in (a) the structural features, (b) morphology and textural properties, such as the pore characteristics, (c) the possible location of Sn4+ ions in the meso silica structure and their reducibility, (d) the nature of the Sn species and their the coordination sphere and (e) the acid-base characteristics. We developed a possible model for the localization of Sn species in SBA-15 pore structure for different conditions of preparation. This report includes our investigations on the catalytic properties of these Sn-SBA-15 samples in 3 industrially important reactions, viz., trans-esterification of diethyl malonate, synthesis of nopol by Prins condensation of beta-pinene with para-formaldehyde and the epoxidation of norbornene. In each of this reaction, while demonstrating the catalytic role of Sn species, we show that the requirement of the type and the environment of Sn species are different for these reactions.
Keywords: mesoporous materials; Properties of Sn-SBA-15; Sn-containing SBA-15; Sn-SBA-15 catalysts; Synthesis of Sn-SBA-15